Paraoxon: An Anticholinesterase That Triggers an Excitotoxic Cascade of Oxidative Stress, Adhesion Responses, and Synaptic Compromise - Karen L.G. Farizatto; Ben A. Bahr (European Scientific Journal, ESJ, 2017)
The anticholinesterase paraoxon (Pxn) is an organophosphate (OP) and the active metabolite of the insecticide parathion. It potently inhibits the enzyme acetylcholinesterase and leads to enhanced glutamate release, diminished GABA uptake, oxidative damage, and neurodegeneration. The resulting increased levels of acetylcholine can trigger seizures and cause neuronal and excitotoxic damage in the brain. The brain susceptibility related to anticholinesterase toxins extends beyond potential brain damage and death from toxic levels of the agent. Asymptomatic low-level exposure to such toxins can also leave the brain vulnerable or even cause it to exhibit neurological problems later in life. The actions of Pxn and similar neurotoxins have been studied in order to examine the events associated with anticholinesterase toxicity in the brain. A recent study demonstrated that Pxn exposure initiates a pathogenic cascade involving seizure events and subsequent signs of damage including unique presynaptic vulnerability and associated behavioral deficits. In addition, Pxn-mediated synaptotoxicity is also associated with enhanced production of oxidative stress as well as integrin adhesion responses. These findings provide a better understanding of the molecular events involved in Pxn toxicity.